PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL TERHADAP MINAT DAN HASIL BELAJAR SISWA KELAS V SDI PANGKABINANGA - A. Dian Islamiati; Alfia Yunita (STKIP Subang, 2024)
Wordwall is an interactive learning media that has been proven effective in attracting students' interest. However, its influence on interest and learning achievement is still an interesting topic for further research. This study aims to empirically test the influence of using Wordwall media on students' learning interest. Using a quasi-experimental research design with a non-equivalent control group, this study compared the learning interest of students who were given learning using Wordwall with a group that used a question box. The results of the study showed a significant influence of the use of Wordwall media on students' learning interest.